USE OF BACTERIAL LYSATE IN COMPLEX TREATMENT OF ACUTE BRONCHITIS COMBINED WITH EUTHYROID SICK SYNDROME IN PRESCHOOLERS - Anastasiia Havrylenko (Eastern Ukrainian Medical Journal, 2022)
Objective. This study’s objective was to determine bacterial lysate’s effect on the state of humoral immunity (IgA, IgM, IgG) in preschool children with acute bronchitis in combination with euthyroid sick syndrome. Materials and methods. We examined 135 children of preschool age (3 to 6 years) with acute bronchitis (main group) and 28 healthy children (control group). Group Ia included 45 children with acute bronchitis who were treated according to the standard scheme. Preschoolers with acute bronchitis in Group Ib (47 patients) additionally received bacterial lysate. Group IIa included 21 children with acute bronchitis and euthyroid sick syndrome (ESS) manifestations who received standard therapy. Group IIb consisted of 22 patients with acute bronchitis and ESS who received standard therapy and were additionally given an immunomodulator. The bacterial lysate consisted of Staphylococcus aureus 6×109 colony-forming units (CFU), Streptococcus pyogenes 6×109 CFU, Streptococcus viridans 6×109 CFU, Klebsiella pneumoniae 6×109 CFU, Klebsiella ozaenae 6×109 CFU, Haemophilus influenzae B 6×109 CFU, Neisseria catarrhalis 6×109 CFU, Streptococcus pneumoniae 6×109 CFU (the latter included the following types in amount of 1×109 CFU each: TY1/EQ11, TY2/EQ22, TY3/EQ14, TY5/EQ15, TY8/EQ23, TY47/EQ24). The effectiveness of bacterial lysate in children with acute bronchitis and with or without ESS was determined by comparing the humoral immunity parameters (IgA, IgM, IgG) in the acute period (1 to 2 days after the onset) and convalescence period (7 to 10 days after the onset). Levels of immunoglobulins (IgA, IgM, and IgG) were measured by solid-phase enzyme-linked immunosorbent assay. All results were statistically processed using the SPSS 26 software. Results. No statistically significant difference was found between the values of immunoglobulins A, M, and G in children with acute bronchitis and with or without ESS manifestations in the acute period of the disease. At the same time, the above parameters were significantly higher than the corresponding values in the control group. A statistically significant difference was observed in the humoral immunity parameters of patients who were given the bacterial lysate vs. patients who were not. In children who were additionally given the bacterial lysate, IgA levels practically equaled the levels of the control group in the convalescence period. The serum levels of IgM and IgG in children who additionally received the immunomodulator tended to approach the values of the control group. Conclusions. The use of bacterial lysate positively affected the restoration of humoral homeostasis, especially on the level of immunoglobulin A, in children with acute bronchitis and with or without the euthyroid sick syndrome. The bacterial lysate demonstrated high efficiency against this disease in this group of patients.